2009
DOI: 10.3163/1536-5050.97.4.015
|View full text |Cite
|
Sign up to set email alerts
|

The Magnet journey: opportunities for librarians to partner with nurses

Abstract: March 2008 ''Introduction to Evidence based Practice in a Magnetic World'' Yancey T, Snow-Croft S: in-person or web-based learning via National Network of Libraries of Medicine Moodle MLA CE www.cech.mlanet.org May 2008 ''Connecting Libraries, Nurses, and Accreditation/Credentialing Organizations to Improve Patient Care'' Sponsored by Hospital Libraries Section and NAHRS, includes papers on MLA white paper, NAHRS surveys, and a play promoting importance of evidence-based nursing (EBN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Research has shown that the evidence-based approach to nursing works best when nurses have access to libraries near clinical settings, current databases and research journals, and the Internet for use in clinical practice (7). Forming a partnership between the library and the Department of Nursing has shown to help raise awareness and increase use of evidence-based…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that the evidence-based approach to nursing works best when nurses have access to libraries near clinical settings, current databases and research journals, and the Internet for use in clinical practice (7). Forming a partnership between the library and the Department of Nursing has shown to help raise awareness and increase use of evidence-based…”
Section: Resultsmentioning
confidence: 99%
“…Information literacy skills are necessary for the successful implementation of evidence‐based nursing and to continuing professional development . As a part of the aim of becoming a Magnet Hospital, KUH in collaboration with the Department of Nursing Science of the University of Eastern Finland has organised a number of extensive in‐service continuing education training programmes in evidence‐based practice for nurses and head nurses. Information retrieval skills training is included in these programmes in order to develop appropriate skills for the nurses to effectively search and find evidence.…”
Section: Interventionmentioning
confidence: 99%
“…found that nurse/librarian collaborations not only increase nurses' knowledge of EBP, but also effectively eliminate barriers to EBP access . These partnerships have been used effectively in past efforts in nursing education and in CE opportunities for licensed staff nurses working in the hospital …”
Section: Introductionmentioning
confidence: 99%
“…17,22 These partnerships have been used effectively in past efforts in nursing education [23][24][25][26] and in CE opportunities for licensed staff nurses working in the hospital. 17,20,[27][28][29] Discussion of outreach to PHNs has been limited within the literature. In 1994, Self et al…”
Section: Introductionmentioning
confidence: 99%